Protocolo de avaliação para embasamento das decisões judiciais, por profissionais da área forense, para crianças e adolescentes acolhidos - Emmendoerfer, Izabella Ross (2014)
The research aimed to create a parental practice protocol to assist in the foundation of judicial decisions that determine the future of children and adolescents who are in institutions cozy. Participated in the survey: two technical teams, comprising: a psychologist, a social worker and a director/manager responsible for the establishment; yet, as the assistant psychologists, one intern psychology course attending the last year; a judge and prosecutor from the Infancy of the Regional Forum of São José dos Pinhais of the District of the Metropolitan Region of Curitiba; six lawyers, a social worker, a guardianship counselor, an educator and a teacher (these, municipal employees). The instruments used in this study were: Protocol Assessment Parental Practices; IEP - Parenting Styles Inventory, EFN-Factorial Scale of Neuroticism and IPSF - Inventory of Family Support. The study identified the global and national historical phenomenon of violence against children and adolescents, correlating facts and Brazilian law. Always adopting an outlook from global to specific, quantified the population of the municipality object of the study, pointed out the main violations of local rights, created a multidisciplinary protocol based on the literature and in law, to be applied to children and adolescents who are if in welcoming institutions, and to be referred to the judicial sphere, assist to adjudicate. The results obtained by applying the protocols were compared with psychosocial reports submitted to the Court for Children. With the first application, remains proven that mothers' acceptance of girl needed psychological treatment, not the infant, the host; in the second, there was the guilt upheld the family, and the inappropriate behavior of the same, featuring psychiatric disorder, was ignored by two host institutions; in the third, remains clear that the supposed reason for the host, "incapable of rape" never happened. Thus, it is concluded that, although protectionist, Brazilian law alone can not change the historical domestic violence suffered by children and adolescents, but the judiciary has the duty to use all available techniques and multidisciplinary scientific knowledge to effectively protect and minimize the suffering of infants, understanding the situation of vulnerability of their families and including them in state aid programs when necessary. Therefore, the training of all actors of the judiciary and the protection network is essential.